Prognosis of second primary oral squamous cell carcinoma after hematologic malignancy: a retrospective cohort analysis - Yu, Huajiao; Li, Bo; Huang, Yu; Zhang, Xue; Zhou, Hanchen; Feng, Zhien; Han, Zhengxue (Frontiers in Oncology, 2025)
BackgroundsPrognosis and optimal management strategies of second primary oral squamous cell carcinoma (OSCC) following a history of hematologic malignancies (HM) remain uncertain. We investigated whether HM history affects OSCC outcomes or necessitates treatment modifications.Patients and methodsThis retrospective cohort study included 2486 OSCC patients: 14 with OSCC as a second primary malignancy post-HM (SPM group) and 2472 with primary OSCC (non-SPM group). Using propensity score matching (PSM), we created two cohorts: 1:17 (13 SPM vs 232 non-SPM) and 1:3 (13 SPM vs 38 non-SPM). Outcomes were disease-free survival (DFS), overall survival (OS), and disease-specific survival (DSS). Survival differences were analyzed using log-rank tests. Multivariate Cox regression identified prognostic predictors.ResultsNo significant survival differences existed between SPM and non-SPM groups in either cohort (1:17: DFS 53.8% vs 68.9%, p=0.102; OS 69.2% vs 81.3%, p=0.170; DSS 69.2% vs 82.2%, p=0.147. 1:3: DFS 53.8% vs 63.2%, p=0.302; OS 69.2% vs 76.3%, p=0.532; DSS 69.2% vs 78.9%, p=0.430). Cox regression identified independent predictors: DFS: Age (p=0.001), T stage (p<0.001), N stage (p<0.001); OS and DSS: Age (p<0.001), T stage (p<0.001), N stage (p<0.001), pathological grade (p<0.001), prior HM was not an independent predictor.ConclusionsA history of HM does not independently predict the prognosis of second primary OSCC nor necessitate modifications to standard OSCC treatment.